IMPLEMENTASI PROGRAM DUTA LITERASI DALAM MENINGKATKAN MINAT BACA SISWA DI SMP NEGERI 4 SURABAYA - Vinaya Andiny Putri; Ahmad Abdullah Zawawi (STKIP Pesisir Selatan, 2026)
This study analyzes the implementation of the Literacy Ambassador Program at SMP Negeri 4 Surabaya as a strategic effort to enhance students' reading interest. Reading interest is a crucial indicator of educational quality and literacy culture at the junior high school level. A qualitative descriptive method with a case study approach was employed. Data were collected through in-depth interviews, participatory observation, and documentation study. The findings reveal that the program, implemented through three flagship activities, significantly impacts students' reading interest. First, L-Box provides easy, varied, and engaging access to reading materials for all school members. Second, Book Review activities stimulate discussion skills and foster critical thinking. Third, the Literacy Wall Magazine serves as a creative expression space and an innovative information source. A structured coaching system also intensively and continuously supports students' competency development. Habituating a reading culture encompassing discipline, perseverance, effective communication, and teamwork contribute to shaping students' positive attitudes. This study confirms that integrating the Literacy Ambassador Program, a continuous coaching system, and a strengthened school literacy culture effectively increases students' reading interest at SMP Negeri 4 Surabaya.